Arabic medicine in China - Buell, Paul D. (Leiden ; Boston)
xii, 993 sayfa
Keywords: “The Huihui Yaofang was an encyclopedia of Near Eastern medicine compiled under the Mongol Yuan Dynasty for the benefit of themselves and the then Chinese medical establishments. Some 15% of the work survives, from a Ming Dynasty edition, and is here translated for the first time into English. We extensively introduce the translation with introductions situating it within the history of western and Chinese medicine, and provide critical apparatus for understanding. We provide accounts of the medicines and foods, with comparisons to other works of the time and to modern folk uses of these medicines in the Middle East. We show that the work is solidly western Asian, specifically derived from Persian-speaking Central Asia, and is adapted to Chinese use in several ways but without losing its western character.“ --